Newspaper office. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows evacuees using a mimeograph machine at the assembly center newspaper office while a young boy reads the "Our Gang" comic strip.